IMPLEMENTASI PERMAINAN JUMBLE WORDS UNTUK MENINGKATKAN KOSA KATA BAHASA INGGRIS SISWA KELAS VI SDN 3 GUNUNG BATU - Nurhayati Nurhayati (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Abstrak. This Community Service (PKM) initiative is to facilitate socialization and training in the utilization of the Jumble Words game as a tool for enhancing English vocabulary among sixth-grade students at SDN 3 Gunung Batu, Ciracap district. The exercise was executed in stages: developing vocabulary resources aligned with the curriculum, elucidating the concepts and rules of the game, and guiding students in direct gameplay practice. The employed method was a participatory approach, when students actively organize random letters into appropriate words according to specific categories or topics. The activity's results indicated a favorable reaction from both students and teachers, characterized by heightened enthusiasm, active participation, and enhanced comprehension of the new terminology. This activity is anticipated to provide as an innovative option for English language acquisition in primary schools.